Expediente Espaço em Revista - Koga, Ana Paula Novais Pires; Matos, Patrícia Francisca; Nazar, Thallita Isabela Silva Martins; Reis, Bruno Serafim dos; Silva, Laira Cristina; Silva, Juniele Martins (Espaço em Revista, 2021)
Expediente Espaço em Revista, v. 23, n. 1, jan./jun. 2021.